2020
DOI: 10.1016/j.cgh.2019.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Early Colonoscopy Does Not Improve Outcomes of Patients With Lower Gastrointestinal Bleeding: Systematic Review of Randomized Trials

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e93. Learning Objective-Upon completion of this activity, successful learners will be able to explain the optimal diagnostic evaluation of a patient presenting with acute lower gastrointestinal bleeding. BACKGROUND & AIMS: Guidelines recommend colonoscopy evaluation within 24 hours of presentation or admission in patients with high-risk or severe acute lower gastrointestinal bleeding (LGIB). Meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…Available evidence comparing early vs. elective colonoscopy in the management of patients with acute LGIB consists of seven systematic reviews with meta-analyses [55][56][57][58][59][60][61], four RCTs [51,[62][63][64], and 16 observational studies [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] (Table 7 s). Patients with "minor" LGIB managed as outpatients and patients with an UGIB source were excluded from the RCTs [51,[62][63][64] and most of the observational studies [66,67,69,[71][72][73][74][75][76][77][78].…”
Section: What Is the Appropriate Timing For Colonoscopy In Patients With Acute Lower Gastrointestinal Bleeding?mentioning
confidence: 99%
“…Available evidence comparing early vs. elective colonoscopy in the management of patients with acute LGIB consists of seven systematic reviews with meta-analyses [55][56][57][58][59][60][61], four RCTs [51,[62][63][64], and 16 observational studies [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] (Table 7 s). Patients with "minor" LGIB managed as outpatients and patients with an UGIB source were excluded from the RCTs [51,[62][63][64] and most of the observational studies [66,67,69,[71][72][73][74][75][76][77][78].…”
Section: What Is the Appropriate Timing For Colonoscopy In Patients With Acute Lower Gastrointestinal Bleeding?mentioning
confidence: 99%
“…The possibility that earlier endoscopic intervention can lead to rapid identification and control of culprit lesion bleeding and consequently could lead to reduced mortality in patients with LGIB makes timing of colonoscopy a critical point and area of interest in management of LGIB. Four RCTs 10 11 13 14 , six observational studies 15 20 21 25 26 27 and seven meta-analyses 28 29 30 31 32 33 34 have been performed to evaluate this issue. One RCT showed that urgent colonoscopy led to identification of a definitive source of bleeding more frequently, but it did not lead to lower mortality 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these strategies were not driven by prepandemic studies regarding the timing of endoscopic intervention, this practice fortuitously has been reflected in emerging literature. 7,8 Returning to basic principles of resuscitation, optimizing medical management, and exhausting alternative diagnostic modalities allows us to focus only on the procedures that are most likely to be therapeutic. COVID-19 infection can mimic or exacerbate the hemodynamic effects of GI bleeding and an effort should be made to discern between the two by administering acetaminophen, intravenous fluid, and blood products as indicated.…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%